Dwelling in mobile times: places, practices and contestations. Issue 3 (3rd May 2016) - Meier, Lars; Frank, Sybille
ABSTRACT: Mobile people dwell in local environments. The present special issue considers the relation between mobility and dwelling. This introduction to the special issue on '(Im)mobilities of dwelling: Places and practices' provides a general introduction to places and practices of dwelling of highly mobile people and discusses why it is a promising subject for both cultural and mobilities studies that still needs to be addressed in its full theoretical and empirical significance. We carve out the state-of-the-art of research regarding (im)mobilities of dwelling and argue that dwelling and mobility are also an issue of power relations and contestations. Against this backdrop we demonstrate that mobility and dwelling are embedded in broader transformations of society, social inequalities and home. Moreover, this introduction demonstrates how the subsequent papers contribute to this integrated perspective on the mobile–immobile nexus.